Adsorptive Detoxification of Congo Red and Brilliant Green Dyes Using Chemically Processed Brassica Oleracea Biowaste from Waste Water - Ayesha Kanwal; Rabia Rehman; Muhammad Imran (Adsorption Science & Technology)
Water pollution being a potential risk to mankind is treated in several ways which includes chemical treatments. Among them, adsorption took a prominent position for the removal of many hazardous dyes from waste water. Here in this study, an environment-friendly, inexpensive, and broadly available leaves of Brassica oleracea were utilized for adsorption of two carcinogenic dyes, i.e., Congo red and brilliant green. The adsorbent Brassica oleracea leaves were collected, dried, and characterized by FTIR and SEM and then utilized in batch manner for dye removal. Isothermal modeling was carried out on data obtained after experiment which show the best fitting of Langmuir with qmax 42.553 and 103.093 mg.g-1 for Congo red (CR) and brilliant green (BG), respectively. Consequently, a homogenous, monolayer mode of adsorption was followed. Kinetic modeling supported pseudosecond order and Elovich model in most suitable manner. It was also found that a spontaneous, exothermic process provided by the values of thermodynamic parameters (∆G°, ∆H°, and ∆S°) was calculated.